Pythium and Phytopythium species associated with weeds collected in vegetable production fields in Brazil. (22nd February 2022) - Barboza, E.A.; Cabral, C.S.; Rossato, M.; Martins, F.H.S.R.; Reis, A.
Abstract: This study aimed to identify Pythium and Phytopythium species from weeds collected in vegetable fields and test their pathogenicity. Weeds with symptoms of damping‐off, root rot or wilt were sampled in the Brazilian states of Ceará, Goiás and Pernambuco, as well as in the Distrito Federal, for isolation and identification of the causal agents. Once isolated, colonies with typical Pythium and Phytopythium characteristics grew in selective V8 medium. Procedures for species identification included morphology and amplification of the ITS and Cox II regions, which were compared with other accessions available at GenBank . The phylogenetic relationships among the isolates and pathogenicity to their original hosts were evaluated. Six Pythium species were identified: P. aphanidermatum, P. oopapillum, P . orthogonon, P. ultimum var. ultimum, P. myriotylum and P. sylvaticum, and two species of Phytopythium, Phy. chamaehyphon and Phy. oedochilum . In the pathogenicity tests, the 10 weed hosts showed symptoms of damping‐off or root rot after inoculation, with exception of Portulaca oleraceae in which none of the isolates was pathogenic. Therefore, common weeds in vegetable fields areas can host different Pythium and Phytopythium species and play an important role in the epidemiology of vegetable diseases, in particular on pathogen survival and population increase. Abstract : Significance and Impact of the Study: The presence of weeds in cultivated areas is a limitation on vegetable production in Brazil. Beyond their competition for water, nutrients and light, weeds may be alternative hosts of plant pathogens, favouring their survival and potential increase in population. In this work, six Pythium and two Phytopythium species were identified infecting weeds collected from vegetable fields in Brazil. Most of these Pythium and Phytopythium species identified are polyphagous plant pathogens, attacking many plant species including many vegetables. This finding has ecological and epidemiological significance indicating weeds can be reservoirs and inoculum sources of pathogens for vegetable crops.